FACTORS AFFECTING COMPLIANCE HEMODIALYSIS PATIENTS - Conny Winata Berikang (POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN MANADO, 2021)
Background: Chronic kidney failure (Chronic Kidney Disease) is a condition of decreased function of the kidneys which is categorized as severe and occurs gradually caused by abnormalities in the kidneys. Efforts to control the patient's fluid intake is an important aspect of life in patients with end-stage chronic renal failure. Adherence to patients undergoing dialysis therapy has positive benefits for these patients, patient adherence to dialysis therapy is closely related to medication adherence, which includes patient adherence to diet, fluid restriction, and making lifestyle changes. Patients with chronic kidney failure have a decreased level of compliance in terms of fluid management. Non-adherence often occurs and is carried out either intentionally or unintentionally Objective: This study was conducted to determine the factors that can affect adherence to fluid restriction in patients undergoing hemodialysis Methods: This study using the literature review method. Analysis of research journals using PIO, for journals for 2017-2021, on Proquest data, google, pubmed. The keywords used were kidney failure, hemodialysis, fluid balance, patient compliance, fluid limitation. The research journals identified were 1,256,158, filtered again and found 23 journals that match the objectives of this study. Research results: the results of the review in this study found age, forgetfulness, self-efficacy, education, family, stress, spirituality as factors that affect patient compliance. Conclusion: three factors that influence patient non-compliance are internal factors, environmental factors, and psychosocial factors. Keywords: Compliance, Internal factors, kidney failure, hemodialysis